2020
DOI: 10.7554/elife.53072
|View full text |Cite
|
Sign up to set email alerts
|

Defining the role of pulmonary endothelial cell heterogeneity in the response to acute lung injury

Abstract: 47Pulmonary endothelial cells (ECs) are an essential component of the gas exchange 48 machinery of the lung alveolus. Despite this, the extent and function of lung EC heterogeneity 49 remains incompletely understood. Using single-cell analytics, we identify multiple EC 50 populations in the mouse lung, including macrovascular endothelium (maEC), microvascular 51 endothelium (miECs), and a new population we have termed Car4-high ECs. Car4-high ECs 52 express a unique gene signature, and ligand-receptor analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
203
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(217 citation statements)
references
References 63 publications
11
203
0
3
Order By: Relevance
“…To date, this approach has been applied to brain 31 , 32 , heart 33 , 34 , kidney 35 37 , liver 38 , 39 , lungs 40 43 , placenta 29 , 30 , 44 , retina 45 and visual cortex 46 . Remarkably, this approach revealed new roles of cells within a tissue 41 and helped explain how ageing 32 , 47 , diseases 34 36 , 48 51 , infections 52 and injuries 31 , 40 , 43 shape multicellular organization. Intercellular crosstalk has been investigated in healthy and diseased liver 50 , kidneys during homeostasis and rejected kidney transplants 35 , 36 , heart during failure and recovery conditions 34 , and healthy and asthmatic lungs 51 .…”
Section: Insights From Rna-based CCI Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, this approach has been applied to brain 31 , 32 , heart 33 , 34 , kidney 35 37 , liver 38 , 39 , lungs 40 43 , placenta 29 , 30 , 44 , retina 45 and visual cortex 46 . Remarkably, this approach revealed new roles of cells within a tissue 41 and helped explain how ageing 32 , 47 , diseases 34 36 , 48 51 , infections 52 and injuries 31 , 40 , 43 shape multicellular organization. Intercellular crosstalk has been investigated in healthy and diseased liver 50 , kidneys during homeostasis and rejected kidney transplants 35 , 36 , heart during failure and recovery conditions 34 , and healthy and asthmatic lungs 51 .…”
Section: Insights From Rna-based CCI Analysesmentioning
confidence: 99%
“…Several studies have incorporated imaging to spatially map cells and integrated transcriptomics to measure CCC. For example, researchers interrogated the communication and response of lung cells to tissue injury 40 , 43 ; spatial information aided the identification of a new population of lung endothelial cells ( Car4 high) and elucidated how these cells communicate with neighbouring alveolar type 1 cells through VEGF signalling given both their proximity and their expression of the cognate genes 43 . Spatial maps have also helped investigate the communication of T cells during their development in the human thymus 13 .…”
Section: Insights From Rna-based CCI Analysesmentioning
confidence: 99%
“…The epithelial cell population was not large enough to separate known distinct lineages. Among the other cellular populations, the extent of endothelial cell diversity (e.g., large vs. small vessel), has been well documented [40].…”
Section: Discussionmentioning
confidence: 99%
“…Teijaro et al have revealed that blocking S1P(1) receptor that is expressed on both endothelial cells and lymphocytes in the lung can suppress CS with reduced mortality in mice infected with human influenza virus (Teijaro et al, 2011). In addition, the lung microvasculature is shown to contain heterogenic endothelial subpopulations with various vasculogenic capacities coordinately contributing to lung injury response (Niethamer et al, 2020;Stevens et al, 2008). Notably, proliferation of the lung endothelial cell subpopulation is enhanced during influenza-mediated lung injury (Basil et al, 2020;Niethamer et al, 2020).…”
Section: Improving Alveolar Gas Exchange By Hdr-induced Vasculature Mmentioning
confidence: 99%
“…In addition, the lung microvasculature is shown to contain heterogenic endothelial subpopulations with various vasculogenic capacities coordinately contributing to lung injury response (Niethamer et al, 2020;Stevens et al, 2008). Notably, proliferation of the lung endothelial cell subpopulation is enhanced during influenza-mediated lung injury (Basil et al, 2020;Niethamer et al, 2020). On the other hand, cutaneous low-dose radiation has been shown to increase tissue vascularity through upregulation of angiogenic and vasculogenic pathways (Thanik et al, 2010).…”
Section: Improving Alveolar Gas Exchange By Hdr-induced Vasculature Mmentioning
confidence: 99%